A ROADMAP FOR ONLINE COURSE DEVELOPMENT TO BLENDED LEARNING OF MASTER STUDENTS - Kaluhin , Ruslan (Physical and Mathematical Education, 2022)
Formulation of the problem. Online education is one of the modern trends that opens up very wide opportunities for lifelong learning. The main concept of online education is an online course - a holistic learning unit characterized by a complete set of goals, content, forms, methods, and tools of learning, operates on the basis of open or partially open Internet access, and is the basis for distance and blended learning. This article attempts to summarize the sequence of actions required to develop an author’s online course. Materials and methods. General scientific methods were used to summarize the views of Ukrainian and foreign scientists on the planning and development of online courses. The modeling method was used to describe one of the stages of developing an online course and designing its technological map. The questionnaire method was used at the stage of determining expectations from the online course "Development of logical thinking of high school students in mathematics." Results. According to the results of the study, the sequence of actions required to create a quality and effective online course was determined. The possibility of introducing an online course as a separate type of independent work for students is substantiated. Three questionnaires have been prepared to provide feedback to the target group of the future online course, namely: a questionnaire on course expectations, a questionnaire for teachers, and a questionnaire for students who successfully complete the course. According to the results of the survey, the first questionnaire identified a list of thematic areas and individual professional competencies that could be of interest to teachers and students majoring in 014 Secondary Education (Mathematics). Conclusions. The developed roadmap is illustrated by the example of a course for professional training of future mathematics teachers but can be extended to an online course of any thematic focus.